Aragonesi, castigliani e catalani: il Mediterraneo di Pero Tafur. - ZINATO, ANDREA (Scripta)
In the course of his travels by land and sea through Italy, the Levant, the Orient and Northern Europe, of which he left precise records in his Andanças e viages, Pero Tafur proves to be an attentive and perceptive observer: not only does he display his technical knowledge enriched by very precise and punctual descriptions of routes, ports, navigation methods, types of vessels and so on, but above all he describes the Mediterranean in which the Aragonese-Catalan, Castilian, Venetian, Genoese and Ottoman fleets clash to impose their military and commercial supremacy. Tafur also recounts the complexity of the Mediterranean world, the geo-political strategies of the maritime powers, the alliances, the wars, the meeting-clash of very different nations and peoples, the customs, even those related to food, the measures to combat plagues and so on. The account of his experiences (with precise references in sources contemporary to him) constitutes a very precious document on the reality of the Mediterranean in the first half of the 15th century.